Aloe-emodin exhibits growth-suppressive effects on androgen-independent human prostate cancer DU145 cells via inhibiting the Wnt/β-catenin signaling pathway: an in vitro and in silico study - Hussain, Talib; Alafnan, Ahmed; Almazni, Ibrahim Abdullah; Helmi, Nawal; Moin, Afrasim; Baeissa, Hanadi M.; Awadelkareem, Amir Mahgoub; Elkhalifa, AbdElmoneim O.; Bakhsh, Tahani; Alzahrani, Abdulrahman; Alghamdi, Rashed Mohammed; Khalid, Mohammad; et al. (Frontiers in Pharmacology, 2024)
At the molecular level, several developmental signaling pathways, such as Wnt/β-catenin, have been associated with the initiation and subsequent progression of prostate carcinomas. The present report elucidated the anti-cancerous attributes of an anthraquinone, aloe-emodin (AE), against androgen-independent human prostate cancer DU145 cells. The cytotoxicity profiling of AE showed that it exerted significant cytotoxic effects and increased lactose dehydrogenase levels in DU145 cells (p < 0.01 and p < 0.001). AE also induced considerable reactive oxygen species (ROS)-mediated oxidative stress, which escalated at higher AE concentrations of 20 and 25 μM. AE also efficiently instigated nuclear fragmentation and condensation concomitantly, followed by the activation of caspase-3 and -9 within DU145 cells. AE further reduced the viability of mitochondria with increased cytosolic cytochrome-c levels (p < 0.01 and p < 0.001) in DU145 cells. Importantly, AE exposure was also correlated with reduced Wnt2 and β-catenin mRNA levels along with their target genes, including cyclin D1 and c-myc. Furthermore, the molecular mechanism of AE was evaluated by performing molecular docking studies with Wnt2 and β-catenin. Evidently, AE exhibited good binding energy scores toward Wnt2 and β-catenin comparable with their respective standards, CCT036477 (Wnt2 inhibitor) and FH535 (β-catenin inhibitor). Thus, it may be considered that AE was competent in exerting anti-growth effects against DU145 androgen-independent prostate cancer cells plausibly by modulating the expression of Wnt/β-catenin signaling.